Forgery of TNI Headquarters Land Documents by Dani Bahdani (A Case Study of Land Dispute Resolution by Unit 3, Sub-Directorate 2, Directorate of General Crimes, Bareskrim Polri) - Axel Theodore Wirasatya Huwae; Chairul Muriman Setyabudi (CV. Proaksara Global Transeduka, 2025)
Land holds a crucial position in Indonesia both as a communal resource and a high-value economic asset, making disputes over land rights particularly those triggered by document forgery highly prevalent and socially impactful. Given this context, cases involving falsified land certificates often escalate into complex legal disputes requiring meticulous investigation. This research aims to analyze the chronology of Dani Bahdani’s lawsuit against TNI Headquarters, the investigation process conducted by Unit 3, Sub-Directorate 2 Directorate of General Crimes, Bareskrim Polri, and the obstacles faced in handling the land document forgery case. Using qualitative methods with a case study approach through interviews, documentation, and source triangulation, the research found that Dani Bahdani used fake girik or Land Ownership Certificate and invalid power of attorney to sue state assets, while investigators successfully uncovered the forgery through investigation management and Scientific Crime Investigation (SCI) including forensic document examination. The research results show that the investigation ran effectively thanks to inter-agency coordination and facility support, but still faced obstacles in the form of weaknesses in the substance of Article 263 of the Criminal Code, lack of synchronization in land regulations, minimal integration of BPN data, and low public legal awareness. In conclusion, this case confirms the importance of strengthening document forgery regulations, integrating the national land system, and increasing legal education to the public to prevent similar cases from recurring.